2006
DOI: 10.1088/1742-6596/33/1/013
|View full text |Cite
|
Sign up to set email alerts
|

Group averaging, positive definiteness and superselection sectors

Abstract: I discuss group averaging as a method for quantising constrained systems whose gauge group is a noncompact Lie group. Focussing on three case studies, I address the convergence of the averaging, possible indefiniteness of the prospective physical inner product and the emergence of superselection sectors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…See [13,15,16,17] for comments on this issue. We are concerned here with generic states, and so will not treat the vacuum in detail.…”
Section: B States With Weak Back-reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…See [13,15,16,17] for comments on this issue. We are concerned here with generic states, and so will not treat the vacuum in detail.…”
Section: B States With Weak Back-reactionmentioning
confidence: 99%
“…[12] showed that this is the case for a 1+1 free scalar toy model and for 3+1 linearized gravitons. While examples (in other contexts) are known for which group averaging is not positive definite [16], these cases are rather singular even at the classical level. Furthermore, when group averaging converges, one can show [21] that it gives the unique physical inner product consistent with the *-algebra of observables on H 0 ; i.e., if it fails to be positive definite, then no renormalized inner product will be positive.…”
Section: A De Sitter Invariant Statesmentioning
confidence: 99%
“…Since group averaging is a technique for taking the action of this observable algebra on H aux and constructing a representation on de Sitter-invariant states, it is clear that the vacuum must be treated separately. See [52,14,53,22,23,24] for more discussion and further examples of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The quantization process will be carried out according to Dirac's approach [39] and employing the so-called group averaging technique [41][42][43][44]. Since this approach does not restrict phase-space variables by means of gauge constraints, the proper-time perspective will be retrieved through the quantization of the proper-time physical variables presented in (11).…”
Section: Proper-time Quantizationmentioning
confidence: 99%